MESSAGES FOR HUMANITY IN "BULA MALINO" (QUIET MOON) (A POEM BY KAIMUDDIN IDRUS MUHAMMADAL-BUTHUNI IBNU BADARUDDIN) - Kamaluddin, K; Rafli, Zainal (INTERNATIONAL JOURNAL OF LANGUAGE EDUCATION AND CULTURE REVIEW, 2015)
"Bula Malino" (Quiet Moon) is a literary work found in Buton society and packaged in the form of poem. The manuscript is written in Wolio Language (Butonese main native language) using an Arabic-Wolio script modification, commonly called "buri Wolio" (Wolio writing). This article is yielded to report findings of a qualitative study which analyzes the humanity messages revealed in the poem using a content analysis and structuralism genetic approach. This approach follows some gradual procedures such as examining intrinsic elements of poem, reviewing social life of author, and giving a reflection to history and social background of Buton society. The findings show that the poem reveals messages and values for humanity in terms of sobriety or calm mind/heart and soul clarity for being prepared for death. The poem also contains advice addressed to readers. It was noted that the author of the poem was born in the late 18th century AD. At the age of 40, he was inaugurated the 29th sultan of Buton. At this century, Buton social condition was more than enthusiastic in learning science. This was marked by the establishment of a school named "Zaawiah".